Modified Vitrectomy Technique for Phakic Rhegmatogenous Retinal Detachment with Intermediate Break - Vincenza Bonfiglio; Mario D. Toro; Antonio Longo; Teresio Avitabile; Robert Rejdak; Katarzyna Nowomiejska; Tomasz Choragiewicz; Andrea Russo; Matteo Fallico; Agnieszka Kaminska; Elina Ortisi; Stefano Zenoni; et al. (Journal of Ophthalmology)
Purpose. To evaluate the effects of a modification of the traditional 25-gauge pars plana vitrectomy technique in the treatment of uncomplicated macula-on rhegmatogenous retinal detachment (RRD) with intermediate retinal break(s) and marked vitreous traction in the phakic eye. Methods. Prospective, noncomparative, and interventional case series. All consecutive phakic eyes with primary uncomplicated macula-on RRD with intermediate retinal break(s) and marked vitreous traction, with at least 1 year of postoperative follow-up, were enrolled. In all eyes, “localized 25-gauge vitrectomy” under air infusion with localized removal of the vitreous surrounding the retinal break(s), in association with laser photocoagulation and air tamponade, was performed. The primary end point was the rate of primary retinal attachment. Secondary end points were cataract progression and assessed by digital Scheimpflug lens photography (mean change of nuclear density units) and the rate of complications. Results. Thirty-two phakic eyes were included in the final analysis. At 12 months, the primary outcome of anatomical success was achieved in 94% of eyes. The mean nuclear density units did not change significantly at any time point during the follow-up. After localized vitrectomy, one eye developed an epiretinal membrane, and one eye developed cystoid macular edema; no other significant complications were reported. Conclusions. “Localized vitrectomy” has a high anatomical success rate in phakic eyes with primary uncomplicated macula-on RRD with intermediate retinal break(s) and marked vitreous traction, without causing progression of cataract.